COVID-19 in India: Epidemiological reflections from initial 170 million consecutive test results - Lohia, Rohan; Goel, Prabudh; Kaur, Jasmine; Kumar, Sujeet; Bajpai, Minu; Singh, Harpreet (Frontiers in Epidemiology, 2022)
The Indian Council of Medical Research (ICMR) played a key role in streamlining testing and diagnosis, formulating guidelines, and devising management strategies during the COVID-19 pandemic. Additionally, ICMR designed and developed a comprehensive data management tool for collecting testing data in a standardized format from all laboratories across the country. The current report is an inference-oriented statistical analysis of the testing data generated by the ICMR for future preparedness. The ICMR data pertaining to the management of the corona-virus pandemic was imported from the data repository of the ICMR, anonymized, and reviewed. The P-to-P (longest time interval between two consecutive positive tests without any intervening negative), P-to-Plast(time between first positive and last positive test), and P-to-N intervals (time between first positive and first negative test) were calculated. India conducted 170,914,170 tests during the study period (till December 29, 2020). After excluding invalid-test-results and duplicates, there were 11,101,603 (6.5%) positive and 156,542,352 (93.5%) negative test-results performed upon 150,086,257 unique individuals. A negative report following a positive test was available in 12.69%. Nearly three-fourths of the cases (78.29%) belonged to the working-age group (18-60 years). The proportion of cases>50 years has risen from 26.06% to 35.03% with a steep rise beyond September-2020. Gender-ratio amongst the positives was 1.73:1 which was neutral in neonates < 7-days (age). The gender ratio was skewed in-favor-of males in the initial months with a reverse trend thereafter and with increasing age of patients. The mean P-to-P, P-to-Plast and P-to-N durations were 12.7+4.3, 13.3+4.6, and 14.2+4.9 days for individuals with P-to-P duration:1-4 weeks. The probability of testing negative was 82% & 85% at 14 & 21 days after the first-positive-test respectively with no gender bias. The current study has highlighted some vital aspects of COVID-19 epidemiology in India. In the absence of pre-existing information on this novel virus and the disease per se, the findings from this study will serve a pertinent role in the formulation of policies & treatment paradigms. They will also be instrumental in improvising upon the existing medical research protocols and formulating newer ones for treatment and research.